(untitled) (Journal of actual problems of jurisprudence, 2019)
Access to information, public participation in decision making and access to justice guaranteed by the Constitution of the Republic of Kazakhstan . In this article, the authors analyzed the legislation of the Republic of Kazakhstan and the ways to implement the Aarhus Convention. Existing legislation of the Republic of Kazakhstan gives the public the right to obtain information , including environmental information , public access to decision-making and justice. Although the legislation of the Republic of Kazakhstan has legislative strengthening , but is necessary to develop specific procedures and mechanisms for their implementation , taking into account the provisions of the Convention. Key words: Aarhus Convention, the law, the right of access to environmental information, public, environmental protection, public access to decision-making and justice.